(untitled) (Journal of actual problems of jurisprudence, 2018)
The given article reviews current issues related to the constitutional guarantees of maternity protection in the Republic of Kazakhstan. Methods of study - a comparative legal, formal and legal, as well as methods of analysis and synthesis. Taking into account current unfavorable situation in the sphere of motherhood and childhood protection, we cannot say that existing constitutional safeguards for the protection of motherhood are effective. Nowadays more large families need better housing conditions. The size of state benefits for child care paid by the government are too low, labor rights of women are often violated, single mothers do not have decent support from the state, the universal access to reproductive health services cannot be fully provided to all of the citizens. Key words: motherhood, the right to motherhood, public protection, protection of motherhood.